Folding of proteins with a flavodoxin‐like architecture. (28th April 2017) - Houwman, Joseline A.; van Mierlo, Carlo P. M.
Abstract : The flavodoxin‐like fold is a protein architecture that can be traced back to the universal ancestor of the three kingdoms of life. Many proteins share this α‐β parallel topology and hence it is highly relevant to illuminate how they fold. Here, we review experiments and simulations concerning the folding of flavodoxins and CheY‐like proteins, which share the flavodoxin‐like fold. These polypeptides tend to temporarily misfold during unassisted folding to their functionally active forms. This susceptibility to frustration is caused by the more rapid formation of an α‐helix compared to a β‐sheet, particularly when a parallel β‐sheet is involved. As a result, flavodoxin‐like proteins form intermediates that are off‐pathway to native protein and several of these species are molten globules (MGs). Experiments suggest that the off‐pathway species are of helical nature and that flavodoxin‐like proteins have a nonconserved transition state that determines the rate of productive folding. Folding of flavodoxin from Azotobacter vinelandii has been investigated extensively, enabling a schematic construction of its folding energy landscape. It is the only flavodoxin‐like protein of which cotranslational folding has been probed. New insights that emphasize differences between in vivo and in vitro folding energy landscapes are emerging: the ribosome modulates MG formation in nascent apoflavodoxin and forces this polypeptide toward the native state. Abstract : The flavodoxin‐like fold is a widespread protein architecture and hence it is highly relevant to illuminate how polypeptides with this architecture fold. We show that these proteins tend to temporarily misfold during unassisted folding in vitro . As a result, off‐pathway intermediates form. In contrast, in vivo the ribosome modulates nascent apoflavodoxin folding and forces this polypeptide toward the native state.